Epidemiology of Poisoning In Hospitalized Children: A 10 Years Cross-Sectional Study in a Teaching Pediatric Hospital, Baghdad, 1993-2002 - Al-Naaimi, Ahmed S; Al-Ani, Nafi A; Alwan, Saleh J; Al-Hadithi, Tariq; Ayoub, Najla I (Journal of the Faculty of Medicine Baghdad, 2008)
Background and Objectives: Poisoning is an important cause of childhood and adolescence hospital emergency presentations and admissions and a major health problem in this population sector. The present study was designed to describe the epidemiology and pattern of poisoning in addition to its case fatality rate. Methods: A total of 1450 pediatric cases with poisoning admitted to the Central Teaching Hospital of Pediatrics, Baghdad, during the 10 years study period extending from the 1st of January 1993 to 31st of December 2002, were analyzed. Results: The peak age for poisoning cases in the present study was 1-4 years, constituting about three quarters of total pediatric admissions with poisoning. Males were more frequent than females in the present work, and this gender bias was more evident in younger ages and less evident in teenagers. Non-medicinal substances were responsible for the major part (threequarters) of poisoning cases, especially petroleum products and pesticides. The overall casefatality rate was 2.6%. The risk of death was higher in the more vulnerable age groups (infants and neonates). It was also higher in males and in cases with poisoning by other noxious substances eaten as food, followed by metals (mainly lead), systemic antibiotics and pesticides. However out of a total of 37 deaths attributed to poisoning that occurred during the present study period of 10 years, non-medicinal substances (especially petroleum products, pesticides and metals) were responsible for three-quarters of these deaths. Conclusion: Children under 5 years of age are the most-vulnerable group for poisoning incidents. In addition Petroleum products, insecticides and lead metal were responsible for the highest proportion of poisoning admission and fatality necessitating special steps directed towards the prevention of these problems.